Multi-organ assessment in mainly non-hospitalized individuals after SARS-CoV-2 infection: The Hamburg City Health Study COVID programme. (6th January 2022) - Petersen, Elina Larissa; Goßling, Alina; Adam, Gerhard; Aepfelbacher, Martin; Behrendt, Christian-Alexander; Cavus, Ersin; Cheng, Bastian; Fischer, Nicole; Gallinat, Jürgen; Kühn, Simone; Gerloff, Christian; Koch-Gromus, Uwe; et al.
Abstract: Aims: Long-term sequelae may occur after SARS-CoV-2 infection. We comprehensively assessed organ-specific functions in individuals after mild to moderate SARS-CoV-2 infection compared with controls from the general population. Methods and results: Four hundred and forty-three mainly non-hospitalized individuals were examined in median 9.6 months after the first positive SARS-CoV-2 test and matched for age, sex, and education with 1328 controls from a population-based German cohort. We assessed pulmonary, cardiac, vascular, renal, and neurological status, as well as patient-related outcomes. Bodyplethysmography documented mildly lower total lung volume (regression coefficient −3.24, adjusted P = 0.014) and higher specific airway resistance (regression coefficient 8.11, adjusted P = 0.001) after SARS-CoV-2 infection. Cardiac assessment revealed slightly lower measures of left (regression coefficient for left ventricular ejection fraction on transthoracic echocardiography −0.93, adjusted P = 0.015) and right ventricular function and higher concentrations of cardiac biomarkers (factor 1.14 for high-sensitivity troponin, 1.41 for N-terminal pro-B-type natriuretic peptide, adjusted P ≤ 0.01) in post-SARS-CoV-2 patients compared with matched controls, but no significant differences in cardiac magnetic resonance imaging findings. Sonographically non-compressible femoral veins, suggesting deep vein thrombosis, were substantially more frequent after SARS-CoV-2 infection (odds ratio 2.68, adjusted P < 0.001). Glomerular filtration rate (regression coefficient −2.35, adjusted P = 0.019) was lower in post-SARS-CoV-2 cases. Relative brain volume, prevalence of cerebral microbleeds, and infarct residuals were similar, while the mean cortical thickness was higher in post-SARS-CoV-2 cases. Cognitive function was not impaired. Similarly, patient-related outcomes did not differ. Conclusion: Subjects who apparently recovered from mild to moderate SARS-CoV-2 infection show signs of subclinical multi-organ affection related to pulmonary, cardiac, thrombotic, and renal function without signs of structural brain damage, neurocognitive, or quality-of-life impairment. Respective screening may guide further patient management. Graphical Abstract: Graphical Abstract The key question is: How does a mild to moderate course of SARS-CoV-2 infection in mainly non-hospitalized individuals impact intermediate-term organ-specific functions in comparison to the general population? The key findings are (i) a mild to moderate course of SARS-CoV-2 infection is associated with subsequent signs of subclinical multi-organ affection; (ii) associations mainly affect the pulmonary, cardiac, coagulation, and renal system; and (iii) no systematic associations with structural brain damage, neurocognition, or quality of life were observed. The take-home message is systematic screening of multi-organ function even after mild to moderate SARS-CoV-2 infection is recommended to identify individuals at risk and initiate appropriate preventive therapies.